Consumo slow fashion e bem-estar: influência da espiritualidade, da gratidão e do materialismo - Araújo Pinto, Liliane (2021)
This thesis had as main objective to analyze the influence of spirituality, gratitude and materialism on well-being, from slow fashion consumption, through the perspectives of positive psychology and transformative consumer research. The theoretical foundation supported the construction of a theoretical model that was tested adopting the techniques of exploratory factor analysis, confirmatory factor analysis and structural equation modeling. 400 followers of Instagram slow fashion profiles were sampled. It was observed that 'spirituality' showed a positive influence on the consumption of slow fashion products that have functionality, exclusivity and are sold by local companies or producers. This was due to the appreciation of products with more versatility, timeless and handcrafted, while 'materialism' had a positive influence on the centrality dimension. This represents, in consumption contexts, that people with characteristics focused on the accumulation of possessions, consider slow fashion products important in their lives, however, these possessions do not generate happiness. Thus, the research contributes by revealing that spirituality and materialism are relevant factors in the decision to consume slow fashion products, despite 'gratitude' not being a strong construct. At the end of the study, the theoretical and practical implications, limitations and suggestions for future research are presented.